Analysis of locational factors affecting high increases in value of residential houses in the northern and southern suburbs of Cape Town - Meelun, Gaushal (Department of Construction Economics and Management, 2022)
Residential property prices in the Western Cape, South Africa, have experienced the highest increase, reaching close to 10% annual increase, in comparison to the rest of the country over the last decade (Lightstone, 2019). Lemanski (2007) further elaborates that residential property prices in Cape Town, in the Northern and Southern Suburbs, have increased by close to 30% from 1980s-late 2000s. This results from the interaction between supply and demand. The demand for property is a function of: need, preference, availability and affordability (Lancaster, 1966). The preference for a particular residential property is in turn determined by internal factors, at a property level, and external factors, at the neighbourhood level. The influence of internal factors such as: land extent, building area, location, number of bedrooms, kitchen and bathroom amongst others, on property prices is well-known. However, the influence of external-locational factors, on residential property prices in the context of South Africa, has been subject of little research. It is argued that, for those who can afford, there is a preference for residential houses which are close to areas that are: well-established, high quality, well controlled, modern hubs for economic activities and central to amenities (Scatigna, Szemere, & Tsatsaronis, 2014; Turok, 2001; Lemanski, 2007; Kotze & Donaldson, 1998; Can 1998). These well-established neighbourhoods are the outcome of past public and private investment, and such neighbourhoods are found in the Northern and Southern Suburbs (Turok, 2001; Lemanski, 2007). Features associated with location, such as the number of offices/business properties, shopping centres, educational institutions, places of worship, medical institutions and residential vacant land, are considered to have an influence on residential house prices and hence contribute to high increases in value in the Northern and Southern Suburbs (Scatigna, Szemere, & Tsatsaronis, 2014; Turok, 2001; Lemanski, 2007; Kotze & Donaldson, 1998; Bardhan, Sarkar, & Kumar, 2016). The findings indicate that the highest concentration of the above-mentioned factors, with the exception of the number of residential vacant land, are found in the Northern and Southern Suburbs. For the Northern suburb, the external factors, the number of: places of worship, business/offices properties and residential vacant land, are recorded to have an influence on the value of residential properties. For the Southern Suburb, the external factors, the number of: places of worship, business/offices properties, shopping centres and medical institutions, are recorded to have an in fluence on the value of residential properties. It is inferred that external factors have an impact on residential property prices and hence have contributed to high increases in value in the Northern and Southern Suburbs. Lastly, it was observed that the Northern and Southern Suburbs are influenced by different combinations of external factors.